2012
DOI: 10.1016/j.tetlet.2012.01.076
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal depsidone metabolites from Cordyceps dipterigena, an endophytic fungus antagonistic to the phytopathogen Gibberella fujikuroi

Abstract: Among thirty four endophytic fungal strains screened for in vitro antagonism, the endophytic fungus Cordyceps dipterigena was found to strongly inhibit mycelial growth of the plant pathogenic fungus Gibberella fujikuroi. Two new depsidone metabolites, cordycepsidone A (1) and cordycepsidone B (2), were isolated from the PDA culture extract of C. dipterigena and identified as being responsible for the antifungal activity. Elucidation of their chemical structures was carried out using 1D and 2D NMR spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…The other signals were attributed to the lactone carbonyl at δ C 166.1 (C-11) and aldehyde function at δ C 193.9 (C-14). These data were similar to those of related depsidones previously isolated from several microorganisms [21,22,23,24] and some species of Garcinia genus [25]. The 1 H NMR spectrum (Table 1) confirmed the presence of two aromatic singlets at δ H 6.85 (1H, s , H-2) and δ H 7.08 (1H, s , H-9), suggesting two penta-substituted aromatic rings.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The other signals were attributed to the lactone carbonyl at δ C 166.1 (C-11) and aldehyde function at δ C 193.9 (C-14). These data were similar to those of related depsidones previously isolated from several microorganisms [21,22,23,24] and some species of Garcinia genus [25]. The 1 H NMR spectrum (Table 1) confirmed the presence of two aromatic singlets at δ H 6.85 (1H, s , H-2) and δ H 7.08 (1H, s , H-9), suggesting two penta-substituted aromatic rings.…”
Section: Resultssupporting
confidence: 86%
“…Allantoin ( 11 ) also displayed weak activity with an IC 50 value of 412.94 μM (Table 3). The activity of compound 1 can be justified by the fact that previous biological studies revealed that depsidones are potential antiviral agents [24]. Furthermore, with reference to compound 1 , previous studies showed that an aromatic moiety next to (at least) two adjacent oxygens appears to be a structural element that is essential for activity against HIV-1 integrase [29].…”
Section: Resultsmentioning
confidence: 99%
“…These metabolites encompass a diverse range of structures including alkaloids [20], terpenoids [21], quinones [22], and peptides, xanthones and phenols [23]. Bioactivity has been observed against cancer cell lines [24] [25], pathogenic bacteria [26] [27] and fungi (e.g., [28]), and against eukaryotic parasites such as the causal agents of malaria, leishmaniasis and Chagas' disease (e.g., [29] [30]). …”
Section: Introductionmentioning
confidence: 99%
“…Figure 2) revealed that the two iso-butyl groups (see above) were attached to the adjoining carbon atoms (C-4 and C-5) of the 2(1H)-pyrimidinone ring. Thus, the structure of this metabolite was determined as 4,5-di-isobutyl-2(1H)-pyrimidinone (2). Although many nucleotides contain 2(1H)-pyrimidinone moieties carrying OH and /or NH 2 substituents, this constitutes the first report of the natural occurrence of a 2(1H)-pyrimidinone bearing non-polar substituents.…”
mentioning
confidence: 89%